Endoscopic diagnosis of a goblet cell carcinoid tumour of the appendix - Falk, Vanessa (BMJ Case Rep, 2018)
Primary malignancies of the appendix are rare. Of these, less than 5% are goblet cell carcinoid (GCC) tumours. The majority of GCC present with findings of acute appendicitis or advanced peritoneal spread. We describe a rare presentation of GCC as subtle mucosal abnormality of the appendiceal orifice seen on colonoscopy performed for iron-deficiency anaemia. Biopsies were interpreted as adenocarcinoma; however, final surgical pathology confirmed GCC of the appendix with caecal involvement. The patient recovered well from surgery, anaemia resolved and follow-up did not show metastatic disease.